A Long-Term Study on the Effect of a Professional Development Program on Science Teachers' Inquiry - Christina Tsaliki; Penelope Papadopoulou; Georgios Malandrakis; Petros Kariotoglou (MDPI AG, 2024)
In this study we explore the effect of a professional development (PD) program on four science teachers' views and practices nearly a year after its completion, regarding inquiry implementation in everyday school practice. The PD program aimed to familiarize participants with current trends in science education (SE), putting emphasis on the inquiry approach. The basic research question guiding this study is whether science teachers' inquiry practices and views changed, and to which extent, long after their participation in the PD program. Teachers' practices were recorded, both during and after the PD, through non-participatory observation and were analysed through a semi-quantitative method. Teachers' views were also recorded both during and after PD through structured questionnaires and reflective interviews, producing qualitative data that were analysed. Findings are encouraging concerning the preservation of guided inquiry practices obtained during the program, while more open inquiry practices proved to be limited. Teachers' views concerning inquiry remained positive, also maintaining their innovative character.